Feasibility study of electrodialysis for vinasse desalting and potassium recovery - Laura Braz Monteiro de Barros (2018)
Brazil is the largest producer of sugarcane in the world, making the sugar and alcohol sector one of the activities of great relevance for the country. In many distilleries the fertigation is adopted, in which the vinasse returns to the crops, bringing beneficial results, however, if applied in excess, it can cause serious negative impacts. Potassium is the predominant ion in the vinasse, and because its high concentration, there are legislations that limit the application of vinasse in agricultural soil. The use of electrodialysis, a membrane separation process in which there is ionic transport under the influence of an electric field, enables, with the reduction of the potassium content of the vinasse, the increase of the rate of application of this effluent already widely used for fertigation, without compromising the soil, the crop and quality of water. In addition, by means of this technology it is possible to concentrate the salts of the vinasse, among which the potassium, enabling its usage as concentrated fertilizer in agriculture. Aspects such as pre-treatment, use of different membranes and configurations and study of different electrolyte solutions with the application focus in the soil were evaluated. Regarding pretreatment, it was observed that ultrafiltration, by removing much of the solids from the vinasse, minimized the inscrustration of the membranes. Three configurations were tested: (1) monovalent selective cationic and anionic membranes, (2) non-monoselective anionic and cationic membranes and (3) mixed configuration (one cationic selective membrane and the others nonselective membranes). The results revealed that the mixed configuration was able to recover, after 8 hours, with a current of 0.11A, 72% of potassium with the lowest energy consumption (0.5 kWh.m- ³) and the best current efficiency (54%). The removal of potassium from vinasse allows an increase of 5 times the dose of vinasse application and consequently reduction of the transport cost in the fields. Solutions of sodium sulfate, magnesium sulfate, ammonium nitrate and potassium sulfate and tap water were tested. Electrolyte solutions of magnesium sulphate and ammonium nitrate provided better conditions, considering greater recovery and removal of potassium and greater potential use of vinasse as fertilizer. The potassium recovery potential of cathodic concentrate in the form of K-struvite was also evaluated and, finally, a primary cost assessment was performed. In this way, in line with the principles of circular economy, the present research project proposes a treatment route for vinasse guided by its valuation through the recovery of by-products and agricultural reuse of water